(untitled) (Bioagro, 2025)
Starting with the current volume (year 2025), we are implementing some minor changes to the formal aspects of the journal. The changes respond to the need to update some styles commonly used in most journals of the area. For example, the clause “et al.” will now be used in italics. Since the journal was created in 1983, the use of normal letters for the clause was adopted. Inertia has maintained this style since then; this, despite the fact that our guidelines for authors order the use of italics for terms written in Latin, or another language with no equivalent in Spanish yet. Another formal adjustment concerns the use of the p for statistical probability. We used to use it as a capital P, and now it will be a lowercase p. Among other adjustments, the definition of the style for writing bibliographical references is still pending. From the beginning, Bioagro used a modification of the Harvard system, the most widely used in science at that time. However, we must migrate to one of the pre-established systems among those existing in the current reference manager softwares, and in this way make it easier for authors to write manuscripts, and standardize the style in all articles. We hope to define the new style to be used soon.